Differential Cytokine Expression and Regulatory Cells in Patients with Primary and Secondary Sjögren's Syndrome. (December 2014) - Furuzawa‐Carballeda, J.; Sánchez‐Guerrero, J.; Betanzos, J. L.; Enriquez, A. B.; Avila‐Casado, C.; Llorente, L.; Hernández‐Molina, G.
Abstract Sjögren's syndrome (SS) is an autoimmune disease characterized by lymphocytic infiltration of the salivary and lacrimal glands. The aim of the study was to characterize and compare the presence of diverse cytokines and regulatory T and B cells in lip minor salivary gland (MSG) biopsies from patients with primary Sjögren's syndrome (pSS), secondary SS (sSS), and patients with connective tissue disease (CTD) without (w/o) SS. We included samples of MSG from 15 pSS, 24 sSS (six scleroderma, nine rheumatoid arthritis and nine lupus patients) and 15 patients with CTD w/o SS. Tissues were examined by an indirect immunoperoxidase technique (goat polyclonal anti‐human IL‐19, goat polyclonal anti‐human IL‐22 or mouse monoclonal anti‐human IL‐24). To determine the subpopulation of CD4+/IL‐17A+‐, CD4+/IL‐4+‐, CD4+/IFN‐ɣ+‐expressing T cells, CD25+/Foxp3+ Treg cells and CD20+/IL‐10+‐producing B cell subset, a double‐staining procedure was performed. We estimated the mean percentage of positively staining cells in two fields per sample. CD4+/IFN‐ɣ+, CD4+/IL‐4+ and IL‐22+ cell percentages were elevated in both SS varieties; however, the cells were more prevalent in pSS. Patients with pSS had a high number of CD4+/IL‐17A+ and IL‐19+ T cells and a lower percentage of IL‐24+ cells (P < 0.05). The Treg and IL‐10‐producing B cells were increased in pSS (P < 0.05). Concluding, in our patients, a pro‐inflammatory and regulatory balance coexists in SS, being both responses more intense in pSS. The explanation of these differences may be related to disease activity, disease duration and treatment.